2016
DOI: 10.1007/s12098-016-2267-z
|View full text |Cite
|
Sign up to set email alerts
|

Quality of Life in Children with Thalassemia and their Caregivers in India

Abstract: Health Related QOL is significantly affected in children with beta-thalassemia major on regular transfusion across all age groups, gender and socio-economic classes and also in their caregivers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
23
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(33 citation statements)
references
References 15 publications
6
23
0
Order By: Relevance
“…The same has been reflected in the study by Sharma S, Seth B et al which focussed on the emotional stress faced by parents in raising their thalassemic child and they found significantly higher proportion of poor health in caregivers than the control group. 1 A study done by Ismail A et al in thalassemic children in Malaysia revealed that the quality of life of thalassemia patients is indeed much lower than the quality of life of healthy controls regardless of age, gender, ethnicity. 9 Majority of parents in this study, (80%) felt disease would hamper child's education as also seen in the study mentioned above.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The same has been reflected in the study by Sharma S, Seth B et al which focussed on the emotional stress faced by parents in raising their thalassemic child and they found significantly higher proportion of poor health in caregivers than the control group. 1 A study done by Ismail A et al in thalassemic children in Malaysia revealed that the quality of life of thalassemia patients is indeed much lower than the quality of life of healthy controls regardless of age, gender, ethnicity. 9 Majority of parents in this study, (80%) felt disease would hamper child's education as also seen in the study mentioned above.…”
Section: Discussionmentioning
confidence: 99%
“…The worldwide prevalence of annually affected conceptions with Beta thalassemia is 42,409 cases with annual births worldwide being 1,28,667,000. 1 High prevalence is present in populations in the Mediterranean, Middle-East, microcytosis and mild anemia. 2 Thalassemia intermediahave atleast 1 beta + thalassemia mutation and is less severe phenotype such that they do not require regular transfusions.…”
Section: Introductionmentioning
confidence: 99%
“…For establishing a causal association, a longitudinal design would have been better, but due to feasibility issue and time constraint, it could not be done. On the other hand, some may argue that case-control design would have been better for the study, as done in some previous studies [37,41]. Still, the researcher thought it would be unethical if CarerQoL of caregivers of thalassemic children (cases) would be compared with CarerQoL of caregivers of healthy children of the same age and sex (controls).…”
Section: Caregivers Sexmentioning
confidence: 96%
“…The data from western India reported a prevalence of up to 9.5% [ 3 ]. Children with beta-thalassemia major have a poor quality of life [ 4 - 5 ]. Similarly, thalassemia is also associated with cardiac complications [ 6 ].…”
Section: Introductionmentioning
confidence: 99%